Assessment of specific cell-mediated immunity to SARS-CoV-2: techniques for its measurement - Enciso-Benavides, Javier (2026)
Understanding the immune response to infection or vaccination against SARS-CoV-2 has become a key objective for the understanding of the disease, its progression, and protection against future infections or possible new variants that may emerge of the virus. The aim of the present review is to focus on the relevance of the cellular immune response and to summarize the different methodologies described for the study of this memory T-cell-related response, either after exposure to the virus or vaccination against SARS-CoV-2. For this purpose, cell proliferation assays (CFSE, 3H-thymidine), cell typing methods (flow cytometry), immunological assays based on the measurement of cytokines (ELISA, ELISPOT, suspension multiplex) and analysis of genes related to cellular immunity by molecular techniques (RT-qPCR or qPCR and sequencing) have been included.